Masonry Walls Reinforced with FRP Bars Subjected to Out-of-Plane Loading (2018)
This article presents the results of a research program on the behavior of masonry walls reinforced with FRP bars subjected to out-of-plane loads. The article also proposes a preliminary protocol for the flexural design of masonry walls reinforced with FRP bars. The objectives of this investigation were: (1) evaluate the flexural behavior of masonry walls reinforced with FRP bars subjected to out-of-plane loads, and (2) develop preliminary design recommendations. Ten masonry walls, 2 m [6.6 ft] high, were subjected to out-of-plane loads, tested under quasi-static loading cycles. The test specimens included walls constructed using concrete and clay masonry units, reinforced with Glass FRP (GFRP) and Carbon FRP (CFRP) bars in different configurations. All the FRPreinforced masonry walls showed a bilinear moment-deflection curve with one steep slope up to cracking of masonry and a decrease in stiffness after cracking. The majority of the walls failed due to crushing of masonry in the compression side. After failure occurred and as the out-of-plane load was progressively removed, the walls returned to a position close to the initial vertical position. In general, the approaches used to calculate flexural strengths and deflections provided good agreement with the experimental results.